Pemberlakuan Sanksi Pelaku Nikah di Bawah Umur - Istianah Ghazali Istianah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This current study aims to discuss child marriage, particularly for the punishment meted out for the perpetrators. This punishment has never received a special attention in the classical Islamic jurisprudence (fiqh) since child marriage is legitimate and not a prohibition, especially according to the four mainstream schools of Sunni jurisprudence (mazhab). However, in the era of contemporary Islam, this marriage is judged to have a negative impact for social life. Through a normative or perspective approach, this study was explored by using several theories, namely: the theories of mukallaf development and law competency (ahliyah) and of uqubah al-ta’zir (punishment of ta’zir). The research results reveal that firstly, child marriage is prohibited due to lack of maturity (rusyd), and immature children are regarded as incapable of having marriage (ahliyah al-ada’ al-naqisah). It indicates that this kind of marriage demonstrates greater negative effects than positive ones, but it is classified into harm li gairih. This category of harm is due to an external factor, namely: marriage is principally declared in Islamic law. Secondly, the punishment meted out for the perpetrators of child marriage is deemed to be in line with the Islamic law. It is due to the fact that in theory of ushl al-fiqh, a prohibition exists as a consequence for the form of ta’zir punishment regulated by the government.